Pancreatitis Secondary to Anti–Programmed Death Receptor 1 Immunotherapy Diagnosed by FDG PET/CT. (November 2015) - Alabed, Yazan Z.; Aghayev, Ayaz; Sakellis, Christopher; Van den Abbeele, Annick D.
Abstract : Abstract: A 57-year-old man with metastatic melanoma developed colitis secondary to ipilimumab, a known immune-related adverse event (irAE). The patient then received pembrolizumab immunotherapy, an anti-programmed-death-receptor-1 (PD-1) antibody. Restaging FDG PET/CT study following 3 cycles of therapy demonstrated diffuse increased FDG uptake throughout the body of the pancreas associated with fat stranding in the peripancreatic region, suggestive of pembrolizumab-induced pancreatitis. Although the patient was clinically asymptomatic, diagnosis was biochemically confirmed with elevated amylase and lipase levels. In the era of immunotherapy, it will be critical to recognize irAEs early to allow prompt initiation of appropriate therapy and reduce the risk of long-term sequelae.